2021
DOI: 10.1177/00222429211023040
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Dark Side of Firm Lobbying: A Customer Perspective

Abstract: Firms spend a substantial amount on lobbying—devoting financial resources on teams of lobbyists to further their interests among regulatory stakeholders. Previous research acknowledges that lobbying positively influences firm value, but it has not examined the parallel effects for customers. Building on the attention-based view (ABV) of the firm, we examine these customer effects. Findings reveal that lobbying negatively affects customer satisfaction so that the positive relationship between lobbying and firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…In contrast, we extend the ABV to study marketing strategy phenomena in general, and a crucial demand-side stakeholdercustomers-in particular. This aligns with newer research (e.g., Vadakkepatt et al 2021) that aligns this theory with customer outcomes. We contribute work on the marketing-finance interface.…”
Section: Theoretical Contributionssupporting
confidence: 74%
“…In contrast, we extend the ABV to study marketing strategy phenomena in general, and a crucial demand-side stakeholdercustomers-in particular. This aligns with newer research (e.g., Vadakkepatt et al 2021) that aligns this theory with customer outcomes. We contribute work on the marketing-finance interface.…”
Section: Theoretical Contributionssupporting
confidence: 74%
“…For example, a firm's lobbying efforts for relaxing emission regulations may affect its brand reputation leading to a decrease in sales. Studies have found that increased spending on lobbying negatively affects customer satisfaction (Vadakkepatt et al, 2021). Therefore, future research should investigate the unintended consequences of political actions applied to supply chain management.…”
Section: Unintended Outcomes Of Political Actionsmentioning
confidence: 99%
“…In our empirical case, and as also evident from the literature and media, brands’ sociopolitical activism and issues are concentrated mostly in the United States (Branicki et al 2021; Hambrick and Wowak 2021; Yang, Saffer, and Li 2020). U.S. firms invest substantially in lobbying efforts in the form of corporate political advocacy (Vadakkepatt et al 2022), and to fill the void in U.S. citizens’ trust in the government, firms take a stance in leadership to align their brands with social causes (Key et al 2021). Thus, the network of U.S. brands and CMOs will expect sociopolitical activism communication more than the network of non-U.S. brands and CMOs, resulting in the latter being less intrigued by and engaged with sociopolitical activism communication.…”
Section: Hypothesis Developmentmentioning
confidence: 99%